Volkanostratigraphy and Petrogenesis of Galunggung Volcano and Surrounding Area, Garut And Tasikmalaya Regency, West Java - Herdiana, Riksan
Galunggung Volcano is an active type-A volcano of Sunda Arc located in Tasikmalaya and Garut Regency, West Java which is located in geografical location 70 12’ 35.61” LS - 70 16’ 58.49” LS dan 1080 03’ 26.81” BT - 1080 10’ 28.55” BT with 104 km2 area. This research aims to study geological setting with the principal of volcanostratigraphy and tectonic setting in the principal of petrogenesis of Galunggung Volcano and the surrounding area. Geomorphological units of research area are divided into six units, which are: Domain I, Domain II, Domain III, Domain IV, Domain V, and Domain VI. Whereas, stratigraphic units are divided into three khuluk, which are: Khuluk Talagabodas, Khuluk Guntur, and Khuluk Galunggung. Within Khuluk Talagabodas there are three gumuk, which are: Gumuk Cikarang, Gumuk Batujahar, and Gumuk Cipatas. Lithologies of those three khuluk and three gumuk are basalt, andecite, pyroclastic breccia, lapillistone, and lahar breccia which are divided into 18 units based on their sources, lithologies (grain size, components’ abundance, and fenocryst), as well as the time of formation. Geological structures observed in research area consist of primary structure of sheeting joint and secondary structure of volcanic normal fault Talagabodas, Guntur, Galunggung, and Cibanjaran. Petrographic texture analysis, anorthite composition in plagioclase, major element variation, and magma saturation shows that there are three phases during magmatic evolution. The first phase (Talagabodas) was commenced and influenced with crystal fractionation. The second phase (Guntur) was influenced with another magma mixing and crystal fractionation. The latter phase (Galunggung) was also influenced with succeeding magma mixing and crystal fractionation. Fenocrysts’ abundance, major elements geochemistry, and trace elements analysis show that magmatic series of the Galunggung Volcano and the surrounding area is Tholeite as subduction in volcanic island arc setting once took place.